Comparative impacts of polyethylene and biodegradable film residues on soil microbial communities and rapeseed performance under field conditions - Xie, MiaoMiao; Wei, Maolu; Sun, Qian; Wang, Ge; Shen, Ting; He, Xinyi; Liu, Dongyan (Frontiers in Microbiology, 2025)
IntroductionSoil health is critical for sustainable agriculture and food security, however, the accumulation of agricultural mulch film residues in soil raises environmental concerns. The effects of conventional polyethylene (PE) and biodegradable (PBAT and PLA) film residues on soil health, microbial communities, and crop productivity under field conditions have not been adequately investigated.MethodsThis study simulated the accumulation of PE film residues from over 30 years of continuous mulching and evaluated PBAT and PLA film residues under field conditions, examining their effects on soil physicochemical properties, microbial communities and rapeseed performance.ResultsThe results revealed that PE residues significantly altered microbial community composition, enhancing the relative abundance of core genera, including Sphingomonas, Acidibacter, and Flavisolibacter, while suppressing other genera, such as Burkholderia-Caballeronia-Paraburkholderia. PE residues also inhibited organic matter decomposition and ureolysis, while limiting nitrate availability and soil fertility, although rapeseed yields remained unaffected. In contrast, biodegradable film residues enhanced soil moisture retention and ammonium content, boosted soil functions such as plastic degradation, nutrient cycling, and chitinolysis, and enriched beneficial genera such as Candidatus Udaeobacter, Acidibacter, and Flavisolibacter, although weakened ureolysis activity. However, both residue types reduced the complexity and stability of the bacterial co-occurrence network, suggesting potential risks to the soil microbial habitats.ConclusionThese findings demonstrate that conventional film residues had no significant effect on rapeseed productivity, whereas biodegradable films exhibited superior performance in maintaining soil fertility and microbial functions under field conditions. Our study emphasizes the need for long-term monitoring to effectively optimize agricultural plastic film applications.